2018
DOI: 10.3390/soils2010005
|View full text |Cite
|
Sign up to set email alerts
|

Species-Specific Impacts of Invasive Plant Success on Vertical Profiles of Soil Carbon Accumulation and Nutrient Retention in the Minjiang River Tidal Estuarine Wetlands of China

Abstract: The increasing presence of successful invasive plant species can have an impact on wetlands capacity to store and release C. We have investigated the relationships between stocks of different soil organic carbon (SOC) along the soil vertical profile and invasive plant success in a China wetland. In stands dominated by the exotic invasive species Spartina alterniflora and the native invasive Phragmites australis soil organic-carbon concentrations (SOC) were higher (12% and 9%, respectively) than in plots of a n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 65 publications
2
10
0
Order By: Relevance
“…As in other studies that have observed differences in bulk density and elemental composition between soils in invaded and native communities (Wang et al, 2018), the causes of these differences in our study were unclear. Nevertheless, this result suggests that the scarcer root system of a tallgrass community, compared with the more consistent root system of a mangrove stand, could have a lower ability to retain small-size particles in the soil, such as clay.…”
Section: The Relationships Between Species Invasion In Mangrove Commentioning
confidence: 51%
“…As in other studies that have observed differences in bulk density and elemental composition between soils in invaded and native communities (Wang et al, 2018), the causes of these differences in our study were unclear. Nevertheless, this result suggests that the scarcer root system of a tallgrass community, compared with the more consistent root system of a mangrove stand, could have a lower ability to retain small-size particles in the soil, such as clay.…”
Section: The Relationships Between Species Invasion In Mangrove Commentioning
confidence: 51%
“…Soil pH and salinity were determined using a multiparameter metre (CyberScan PC 300), after equilibration of soil with deionized water (soil: water, 1:5) [35,36]. Soil N content was determined using Kjeldahl digestion procedure [35,36].…”
Section: Collection and Analysis Of Soil Samplesmentioning
confidence: 99%
“…Soil pH and salinity were determined using a multiparameter metre (CyberScan PC 300), after equilibration of soil with deionized water (soil: water, 1:5) [35,36]. Soil N content was determined using Kjeldahl digestion procedure [35,36]. Bulk density (Db) was determined by drying a known volume of soil sample (determined from the dimensions of the core) at 105 °C until it reached a constant weight, cooled to room temperature in a desiccator, and weighed again.…”
Section: Collection and Analysis Of Soil Samplesmentioning
confidence: 99%
See 1 more Smart Citation
“…Quantifying the effects of S. alterniflora invasion on SOC storage and its vertical distribution is thus an important task for carbon accounting and coastal protection. Some previous studies on the responses of SOC dynamics to S. alterniflora invasion have shown that the introduction of S. alterniflora has led to an increase in SOC storage (e.g., Liao et al, ; Wang et al, ; Yang et al, ; Yuan et al, ; Zhang et al, ). A primary mechanism for the net accumulation of SOC in wetlands is the rising quantity and quality of biomass inputs in soils influenced by S. alterniflora (Liu et al, ; Yuan et al, ).…”
Section: Introductionmentioning
confidence: 99%